Financial system and the industrialisation of Japan: 1900-1970 - TERANISHI, J. (PSL Quarterly Review, 2013)
This article examines the role of the Japanese financial system in the industrialisation of Japan over the period 1900-1970. The author explores the role of a financial system in the development of an industrialising economy and considers the pre-war and post-war financial system in Japan, arguing that although it underwent great transformations, the merits and demerits of each particular system must be viewed in terms of its current environment. JEL: N15, N25, O14